Microwave-Assisted Synthesis, in silico ADME Prediction and Antibacterial Study of 2-(Substituted acetamido)-5-Nitrobenzophenone Derivatives - Li, Tiangang; Singh, Sandeep; Zhai, Xing; Meng, Xiangqi; K. Singh, Rajesh (Asian Journal of Chemistry, 2015)
A series of novel 2-amino-5-nitrobenzophenone derivatives (3-10) were synthesized and characterized by IR, 1H NMR and CHN elemental studies. All the synthesized compounds were subjected to in silico ADME predictions for determination for drug like properties. The values of physico-chemical parameters like molecular weight, nON value, nOHNH value, n-violations and the number of rotatable bonds of all the synthesized compounds also lies between the ranges that are required for good bioavailability. The synthesized compounds were tested for their in vitro antibacterial activity against the Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. Among all the compounds synthesized compounds 4, 9, 10 have shown the maximum antibacterial activity in their group whereas compounds 3, 6, 8 have shown the minimum antibacterial activity.